Student Interest in Traditional Sports in the Era of Society 5.0 - Munawar, Ahmad Al; Girsang, Diego Gunawan; Sugiarto, Dimas; Sitorus, Delima Lestari; Devira, Devira; Syahbana, Muhammad Ali; Pangestu, Dipa; Habibi, S. Ahmad (Pusdikra-Publishing.com, 2024)
Given the strong connection between physical activities, such as sports, and factors like quality of life, health, and overall well-being, it is crucial for every person to cultivate an interest in sports. Many sports that are popular throughout the community are categorised as